Features of the Polish Experience Application in Legal Labor Migration Regulation in Ukraine - Horot, A.; Гороть, А.; Prokopchuk, K.; Прокопчук, К. (Волин. нац. ун-т ім. Лесі Українки, 2018)
In this article we try to characterize and analyze the peculiarities of the migration policy development in the early 90's of the twentieth century and till the present day, since today it is expedient for Ukraine to study the Polish experience in order to borrow and successfully implement certain elements and principle approaches in solving the problems. An import ant component in shaping the Ukrainian-Polish relations in the field of migration is the improvement and expansion of the legal and contractual frame work in this area. It is for this purpose to analyze and characterize, from the point of view of national law and international law, the formation legal and organizational principles of the Ukraine migration policy on the example of the Republic of Poland since it has gained independence. У статті зроблено спробу охарактеризувати та проаналізувати особливості розвитку міграційної політики з початку 90-х ХХ ст. і до сьогоднішніх днів, оскільки Україні сьогодні доцільно вивчити польський досвід для запозичення та успішного впровадження певних елементів міграційної політики і принципових підходів до вирішенні подібних проблем в Україні. Важливим компонентом у формуванні українсько-польських відносин у сфері міграції є вдосконалення та розширення правової та договірної бази. Саме з цією метою зроблено спробу проаналізувати та охарактеризувати формування правових та організаційних принципів міграційної політики України на прикладі Республіки Польща з часу набуття нею незалежності, з точки зору як національного права так і міжнародного права.
Особливості застосування в Україні польського досвіду правового регулювання трудової міграції
Keywords: strategic partner; bilateral cooperation; foreign policy activit; international cooperation; migration; migration policy; Ukraine, Republic of Poland; migrant workers; labor migration